2014
DOI: 10.1371/journal.pone.0101991
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic Activity of Sulforaphane in Primary Blasts from Patients Affected by Myelo- and Lympho-Proliferative Disorders and in Hypoxic Conditions

Abstract: Sulforaphane is a dietary isothiocyanate found in cruciferous vegetables showing antileukemic activity. With the purpose of extending the potential clinical impact of sulforaphane in the oncological field, we investigated the antileukemic effect of sulforaphane on blasts from patients affected by different types of leukemia and, taking into account the intrinsically hypoxic nature of bone marrow, on a leukemia cell line (REH) maintained in hypoxic conditions. In particular, we tested sulforaphane on patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…Moreover, in human being, sulforaphane displays the multiple interesting biological functions: such as anti-cancer effects (Li et al, 2011;Amin and Shankar, 2015;Dandawate et al, 2016;Leone et al, 2017;Jiang et al, 2018;Sita et al, 2018), antioxidant functions (Negrette-Guzman et al, 2013), anti-Helicobacter pylori activity (Yanaka, 2017), photo aging prevention (Sikdar et al, 2016), prevention of obesity (Martins et al, 2018), and general health benefits (Vanduchova et al, 2019). On the other hand, although numerous reports concerning to the chemopreventive and chemotherapeutic properities of solid tumors are available, there is little information on the properities of sulforaphane in leukemia cells (Choi et al, 2008;Fimognari et al, 2008;Suppipat and Lacorazza, 2014;Fimognari et al, 2014;Shih et al, 2016;Shang et al, 2017;Brown et al, 2017;Koolivand et al, 2018). Unfortunately, the understanding of the effects of sulforaphane on human leukemia cells with mechanisms is incompletely explored till now.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in human being, sulforaphane displays the multiple interesting biological functions: such as anti-cancer effects (Li et al, 2011;Amin and Shankar, 2015;Dandawate et al, 2016;Leone et al, 2017;Jiang et al, 2018;Sita et al, 2018), antioxidant functions (Negrette-Guzman et al, 2013), anti-Helicobacter pylori activity (Yanaka, 2017), photo aging prevention (Sikdar et al, 2016), prevention of obesity (Martins et al, 2018), and general health benefits (Vanduchova et al, 2019). On the other hand, although numerous reports concerning to the chemopreventive and chemotherapeutic properities of solid tumors are available, there is little information on the properities of sulforaphane in leukemia cells (Choi et al, 2008;Fimognari et al, 2008;Suppipat and Lacorazza, 2014;Fimognari et al, 2014;Shih et al, 2016;Shang et al, 2017;Brown et al, 2017;Koolivand et al, 2018). Unfortunately, the understanding of the effects of sulforaphane on human leukemia cells with mechanisms is incompletely explored till now.…”
Section: Introductionmentioning
confidence: 99%
“…In high‐risk ALL patients, SFN can act as an adjunctive agent to improve the therapeutic response (Suppipat et al, ). SFN might be used against malignancies and broader population of leukemia patients (Fimognari et al, ). The effects of SFN on apoptosis in HL‐60 cells are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SFN has been shown to inhibit the progression of benign to malignant tumours by way of inhibition of angiogenesis and metastasis . The mechanisms elucidated have included inhibition of MMP‐2 and ‐9 in B16F‐10 melanoma cells in C57BL/6 mice and downregulation of MMP‐1 and ‐2 in YD10B oral carcinoma cells .…”
Section: Discussionmentioning
confidence: 96%
“…The formation of reactive oxygen species (ROS) in SFN‐treated cells was evaluated with the probe dihydrorhodamine and was found to be cell‐line specific, with a generation of ROS seen in the OS 2.4 cell line and a quenching of ROS in the HMPOS cell line. Several studies have shown SFN‐induced formation of ROS is associated with single and double strand DNA breaks before apoptosis occurs . On the contrary, Rudolf et al showed that the pro‐apoptotic effects of SFN on SW620 human colon carcinoma cells does not depend on ROS .…”
Section: Discussionmentioning
confidence: 99%